World History - Kordas, Ann; Lynch, Ryan J; Nelson, Brooke (Open textbook library.)
World History, Volume 1: to 1500 is designed to meet the scope and sequence of a world history course to 1500 offered at both two-year and four-year institutions. Suitable for both majors and non majors World History, Volume 1: to 1500 introduces students to a global perspective of history couched in an engaging narrative. Concepts and assessments help students think critically about the issues they encounter so they can broaden their perspective of global history. A special effort has been made to introduce and juxtapose people’s experiences of history for a rich and nuanced discussion. Primary source material represents the cultures being discussed from a firsthand perspective whenever possible. World History, Volume 1: to 1500 also includes the work of diverse and underrepresented scholars to ensure a full range of perspectives.